Effects of Omeprazole and Caffeine Alone and in Combination with Gentamicin and Ciprofloxacin Against Antibiotic Resistant Staphylococcus Aureus and Escherichia Coli Strains - Bibi Sedigheh Fazly Bazzaz; Mahmoud Fakori; Bahman Khameneh; Hossein Hosseinzadeh (Korean Pharmacopuncture Institute, 2019)
Objective: Antibiotic resistance is a global health problem and threatens health of societies. These problems have led to a search for alternative approaches such as combination therapy. The aim of the present study was to investigate the effect of caffeine and omeprazole in combination with gentamicin or ciprofloxacin against standard and clinically resistant isolates of Staphylococcus aureus and Escherichia coli. Methods: The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values of different agents against bacterial strains were determined. The interaction of non- antibiotic drugs with gentamicin and ciprofloxacin was studied in vitro using a checkerboard method and calculating fraction inhibitory concentration index (FICI). Verapamil as efflux pump inhibitor was used to evaluate the possible mechanism of bacterial resistance to antibiotics. Results: The MIC and MBC values of gentamicin against bacterial strains were in the range of 20- 80 μg/ml and 40-200 μg/ml, respectively. Caffeine and omeprazole had no intrinsic inhibitory activity against tested microorganisms. However, upon combination of caffeine with antibiotics, the synergistic effects were observed. Verapamil was able to reduce the MIC values of gentamicin (4 folds) only in some bacterial strains. Conclusion: These findings indicated that caffeine was effective in removing bacterial infection caused by S. aureus and E. coli. The relevant mechanisms of antibiotic resistance were not related to the drug efflux.